STABILITAS KONSENTRASI GLUKOSA DARAH SIMPAN JANGKA PENDEK DALAM TABUNG BERTEKNOLOGI PEMISAH JELl - Ayi Furqon; Hilman Nurmukhlis; Sussylawati Kasiman (Pharmaciana, 2015)
Serum glucose level is screening for diabetic patients. Preanalitical factors such as sample preparation and handling will influence the quality of final result of determination. Gel sparation technology used for faster sparation between plasma or serum and blood cells. This technology was applied in clinical laboratory technology in stead of public health laboratory. Requested test of glucose level determination is higher then other analytes. Direct contact of blood cells to serum will reduce availability of glucose in serum due to glycolysis process as well as without additional enzyme inhibitors such as fluoride and without separating cells from serum immediately. Serum separating Tube (SST) contains gel and clot activators, it will work faster than plain tube does to become serum. Main purpose of research, how stability of glucose level between SST tube and plain tube . Experimental steps are preparing fresh blood that is collected from 16 voluntered students, incorporating the glucose oxidase enzymatic assay and quality control. Test performed at immediately, late 4 hours, and very late 12 haours. Statistical method for the time to time analysis, one way Anova is used within significant level 0.05. From 16 serum (duplicates), glucose serum level was reduced early at 4 - 12 hours by 8,1 mg/dl (p-value = 0.013) and 7,7 mg/dl (p-value 0.012). Percents increases of glucose level within plain tube 4 hours by 4,75% and within 12 hours by 13,12%. The increased serum glucose level in SST tube were at early 4 hours and 12 hours by 4,33% and 12,29% respectively. Conclussion, glucose serum level is in steady at room temperature until 4 hours for both SST Tube as well as plain tube